The Influence of Utilitarian Motivation, Ideal Self-Concept, and Perception of Consumers on Intention to Use Islamic Banking Products - Sarah Barqiah; Endy Gunanto Marsasi (Jurnal Organisasi dan Manajemen, 2022)
Purpose – This research determined the influence of utilitarian motivation, ideal self-concept, and consumers' perceptions on intention to use Islamic banking products by identifying their characteristics as Muslims. Methodology – This is a quantitative research with primary data collected from a sample of 367 respondents, selected using a purposive sampling method through a survey method. The data collected were analyzed using a Likert scale of 1-5 to go through the SEM test. Findings – It critically examined the utilitarian motivation to focus on research gaps and to determine evidence of the effect of the ideal self-concept capable of increasing intention to use. The result shows that both factors affect the intention to use. Originality – This research collaborated with two theories, namely functional attitude and self-concept. Contributions were added in the form of an ideal self-concept and the researchers’ relationship to utilitarian motivation.